Tinkering alone and together: Tracking the emergence of children's projects in a library workshop. (September 2019) - Parekh, Priyanka; Gee, Elisabeth R.
Abstract: The Maker Movement has inspired educators, mentors, and parents to teach and learn with children through a wide range of activities called making. This article describes children's ways of problem solving while engaging in a special kind of making described as tinkering using a broad constructionist (Papert, 1983) theoretical perspective of learning as active meaning making while building constructions. We present three tinkering projects created by children along with the emergent problem-solving associated with each project. Each case is unique in terms of the tinkering and problem-solving process, nature of materials used, and the social interactions that support it. Our findings indicate how tinkering projects mediate the intersection of personal and public, physical and intellectual, and enable the navigation of material, social, and intellectual domains. These findings are situated in existing research in the area of problem solving while designing and tinkering, and implications for future learning are considered.